(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3ehghH Hf CMeO Hf eMeO Hf GdNVQ GdLhGdjbj s)
(3ChdgG (B:s
(3HGH GdMeGSI bGd QLd ef HdYfHQ ef Hfj Jeje jbGd dg bQjW Hf Cfja ESdGej dh cfJ ef eGRf de JSJHM EHdj Hfh GddbjWI ef Pgd Hf TjHGfG s
(3BNQgG (B:s
(3Ydi fZGfZ SGdJ aj jdGYegG cKjQI GdhTi aj djf hJQajb cCfeG djSJ Ch CdHSJ afcG abdUJ MhGTjg Yf GdShb s
(3GfXQ GdLRA GdChd HQbej (B307s
308 (3JMJ YfhGf OjhGf GdMeGSIs
(3LeY ajg eG GNJGQg ef CTYGQ GdYQH hQJHg Ydi YTQI CHhGHs
(3hYdi GdfSNI bQGAI GdLhGdjbj Ydi TjNg GdJHQjRj HSfOg Edi CHj JeGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
Keywords: (3GdCOHs